(untitled) (Research, Society and Development, 2022)
Introduction: Finding the perfect and harmonious smile has everything to do with facial aesthetics. As a result, patients express a desire for natural-looking restorations, as clean, well-contoured, straight teeth set standards for beauty. With the appearance of adhesive and restorative materials, mainly composite resins and ceramics, procedures that are becoming increasingly reliable have been performed. Objective: The objective of the present study was to carry out a literature review on the predictability of esthetic restorations in composite resin and ceramic, pointing out their main advantages, disadvantages, success factors and main reasons for failure that will influence their clinical longevity. Methodology: This article is a narrative literature review, which is based on bibliographic research with a qualitative approach. Initially, a bibliographic search of scientific articles published through the Google Scholar database and Research Society and Development Magazine will be carried out. For a correct design in the search for articles, health descriptors (DeCS) were used. The research will be limited to articles published in Portuguese, including a publication interval between the years 2003 to 2022. Conclusion: It is concluded that both materials used in this case, ceramics and composite resin, provide satisfactory results for the restoration esthetics of anterior teeth.